Pembentukan dan Makna Gitaigo dalam Komik Handa Kun Karya Satsuki Yoshino - Ariesta Cakadha Meganing, Ni Nyoman; Budiana, I Made; Rauh Artana, I Nyoman (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2019)
The title of this research is “Formation and Meaning on Gitaigo of Handa Kun Comic by Satsuki Yoshino” that aimed to explain the forming process and meaning on gitaigo of Handa Kun comic 1-7 volume by Satsuki Yoshino. The problem in this research was analyzed by using formal method and informal technique. Gitaigo formation analysis used Japanese morphology theory by Tsujimura (1996) and characteristic of Japanese onomatopoeia by Akimoto (2002). While the gitaigo meaning analysis used semantic property theory by Chaer (2015a). The result of this research is on Handa Kun comic was found three types of gitaigo formation i.e. reduplication, affixation, and compounding. Furthermore, the characteristic of onomatopoeia that found are hanpuku, sokuon, choo’on, hatsuon, and -ri morpheme addition. Then, inheritance elements and additional elements was found in each gitaigo. Through additional elements found, there is an expansion meaning or constriction meaning can be known in the words that formed by gitaigo.